2003
DOI: 10.1016/s1063-4584(03)00028-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine inhibits IL-1β-induced NFκB activation in human osteoarthritic chondrocytes

Abstract: GS inhibits the synthesis of proinflammatory mediators in HOC stimulated with IL-1beta through a NFkappaB-dependent mechanism. Our study further supports the role of GS as a symptom- and structure-modifying drug in the treatment of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
282
3
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(313 citation statements)
references
References 33 publications
16
282
3
12
Order By: Relevance
“…Isolation of PBMCs was done by Lymphoprep separation (28), and cell pellets were lysed in hypotonic buffer for nuclear protein isolation (35) or in TRIzol reagent (Life Technologies, Gaithersburg, MD) for RNA extraction. Protein extracts pooled from mononuclear cells were prepared as described previously (28), and the concentration was quantified by the bicinchoninic acid method (Pierce, Rockford, IL).…”
Section: Serum Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of PBMCs was done by Lymphoprep separation (28), and cell pellets were lysed in hypotonic buffer for nuclear protein isolation (35) or in TRIzol reagent (Life Technologies, Gaithersburg, MD) for RNA extraction. Protein extracts pooled from mononuclear cells were prepared as described previously (28), and the concentration was quantified by the bicinchoninic acid method (Pierce, Rockford, IL).…”
Section: Serum Chemistrymentioning
confidence: 99%
“…Protein extracts pooled from mononuclear cells were prepared as described previously (28), and the concentration was quantified by the bicinchoninic acid method (Pierce, Rockford, IL). A consensus oligonucleotide for NF-B (Promega, Madison, WI) was 32 P end-labeled using 10 units of T4 polynucleotide kinase (Promega), and nuclear extracts were equilibrated in binding buffer (35) before adding the labeled probe. The specificity of the assay was tested by preincubating the samples with a 100-fold excess of unlabeled probe (competitive control).…”
Section: Serum Chemistrymentioning
confidence: 99%
“…At the cellular level, GlcN inhibits interleukin-1␤ (IL-1␤)-induced nuclear factor-B (NF-B) activation in chondrocytes (10,11). As well, GlcN inhibits lipopolysaccharide (LPS)-induced NO production in RAW 264.7 macrophages and microglia (10 -14).…”
mentioning
confidence: 99%
“…Various cytokines such as nitric oxide, PG, interleukin-1β, tumor necrosis factor-α, interleukin-6 and interleukin-8 are expressed in higher proportions in the chondrocytes of OA patients [6,9]. Chondrocytes play an important role in the onset of pain during inflammation by activating the neurons [7,16]. Studies have demonstrated that the expressions of interleukin-4, tumor necrosis factor-α, interleukin-6, and interleukin-13 are promoted by P2X7R activation [17].…”
Section: Discussionmentioning
confidence: 99%
“…The development and progression of OA are induced by the expression of cytokines through alteration in the equilibrium between formation and degradation of chondrocytes [6]. Up-regulation of interleukin-13 leads to the breakdown of cartilage matrix and affects chondrocyte function [6,7]. The chondrocytes and synovial membrane of OA patients express higher level of interleukin-1β, interleukin-6, tumor necrosis factor-α and prostaglandin E2 [8].…”
Section: Introductionmentioning
confidence: 99%